Myroides odoratus central nervous infection in a postneurosurgery patient - Vivek G Bhat; Hemant J Vira; Prakash Shetty; Sudeep Gupta (Indian Journal of Medical and Paediatric Oncology)
The organisms belonging to the genus Myroides are ubiquitously present in the environment and have been implicated in infections in immunocompromised patients. We report the recent isolation of Myroides odoratus from the cerebrospinal fluid (CSF) of a patient with anaplastic astrocytoma in the right frontal lobe who had undergone a supratentorial craniectomy for a recurrent right frontal tumor. The organism was identified by the VITEK-2 automated identification system (BioMérieux, Marcy-l'Étoile, France) in addition to microscopic morphology, cultural characteristics, and biochemical tests. The recovery of pure culture of M. odoratus from CSF culture and the patient's clinical response to treatment with cefoperazone–sulbactam support its potential etiological role. M. odoratus can be a causative agent of postneurosurgery central nervous system infection and is amenable to treatment with appropriate antibiotics.